Sosialisasi 1000 HPK Sebagai Upaya Pencegahan Stunting Pada Balita Di Kabupaten GorontaloSosialisasi 1000 HPK Sebagai Upaya Pencegahan Stunting Pada Balita Di Kabupaten Gorontalo - Ramadhani, Firdausi; Igirisa, Repin; Abdullah, Rizky R.; Akuba, Tia Putri Cecilia; Ain, Nur; Senewe, Andriyani Nur Fadillah; Bokings, Sri Ratu Liana; Aneta, Anggrainy Sucitra; Adipu, Alya Adipu; Latukolan, Andini Novianti; Dukalang, Fajrin A.; Ibrahim, Sri Yayun (Universitas Gorontalo, 2023)
The province of Gorontalo has experienced stunting reaching 32%, so seriousness is needed in dealing with stunting problems. Especially in Tenggela Village, Tilango District, Gorontalo Regency, there are 25 babies with stunting. The implementation method used in counseling activities records infants/toddlers affected by stunting. The counseling was attended by 25 parents who had babies/toddlers suffering from stunting, which were divided from hamlet 1 and hamlet 2. Long-term malnutrition, especially in the first 1000 days of life, can cause growth failure. Stunting that occurs if it is not balanced with catch-up growth can result in decreased growth, public health which is associated with an increased risk of morbidity, death and obstacles to growth both motoric and mental. Based on the results of an analysis of the general characteristics of toddlers obtained, higher stunting was found in toddlers aged three years when compared to toddlers aged four and two years. The incidence of stunting is also higher in toddlers who are exposed to cigarette smoke. Based on the habit of washing hands of parents before interacting with toddlers, higher stunting was found in parents who had a habit of washing hands with soap. Therefore, the influence of environmental factors and parental behavior on stunting sufferers can show the results of the analysis that not boiling drinking water, unsanitary housing conditions, and ownership of unsanitary latrines are not risk factors for stunting.Â Keywords: infants/toddlers, counseling, stunting